PROJECT MANAGEMENT CHALLENGES IN PUBLIC SECTOR IT: A CASE STUDY IN PALU - Mutia Sayyidah; Teguh Raharjo; Ni Wayan Trisnawaty (Fakultas Teknik dan Informatika Universitas PGRI Mahadewa Indonesia, 2026)
Public sector IT projects frequently encounter challenges that impede successful delivery, especially in decentralised environments. This study explores the key project management issues that emerged during the development of the Kelurahan Cantik (Smart Statistical Village) website in Palu, Indonesia. Employing a mixed-method case study, we combined the PMBOK 7th Edition framework with empirical ICT project failure factors to evaluate the project’s planning and execution. Quantitative data were collected through a structured Likert-scale questionnaire completed by 30 respondents involved in the project, while qualitative insights were drawn from document analysis. The findings highlight critical gaps in stakeholder engagement, project monitoring, and leadership support, along with inadequate user preparation and technological misalignment. These issues significantly affected project outcomes, particularly in terms of system utilisation and benefit realisation. This study offers practical recommendations for strengthening governance, planning, and stakeholder coordination in future local government IT initiatives